The idea of justice at the service of development in Amartya Sen (2010)
From the most recent work of Amartya Sen, this text is a review of the struggle between self-interested and altruist reasons as a development foundation in justice as a background. Based on contributions from John Rawls and Douglass North, it proposes a n